Structure of application of inertial functional loads on kinematic and dynamic running performance in the phase of maximum speed athletes: an electromyographic study - Zecirovic, A.; Bjelica, B.; Preljevic, A.; Zecirovic, R. (American Journal of Sports Science, 2021)
The aim of this research was to induce changes in the kinematic and dynamic performance of running at maximum speed within the training with the application of additional inertial load, as well as to determine the adaptation processes in the observed variables that are supposed to significantly affect the maximum running speed. The research included initial and final measurement of all variables. Both measurements were performed in two days, the initial measurement (pretest) one day before the start of the training procedure, and finally two days after the end of the training procedure. Measurement of dynamic and kinematic variants was realized when running at maximum speed on the track from the 25th to the 50th meter. Each respondent ran twice, and a better score was used for the final treatment. Measuring devices (photocells - Brower timing system) are placed at the start, so that they register the start from the place (0.5m), at 25m and finally at 50m. Values were measured with an accuracy of 0.01s. The change of kinematic variables recorded by non - contact telemetry measurement (two - dimensional system) of one step cycle during the sprint step in the phase of maximum running speed, and as a consequence of applying a programmed training procedure with additional load at two different locations, was analyzed. The obtained results indicate that the applied experimental factor within a specific six-week period caused statistically significant changes in the experimental (ER) and (EN) groups.